Bentuk, Makna, dan Fungsi Sastra Lisan Pujian di Kelurahan Bugul Lor Kota Pasuruan - Mahmudah Mahmudah (Universitas Nusantara PGRI Kediri, 2021)
Study in this research is the form, meaning, and function of the oral literature of praise that is sung after the call to prayer and before performing the prayers. The purpose of the study entitled